Analisis Penyelesaian Sengketa Pemilihan Kepala Desa di Indonesia - Adhi Putra Satria (Universitas Muhammadiyah Purwokerto, 2020)
This study aims to provide knowledge about how to resolve village head election disputes in Indonesia after the issuance of Law No. 6 of 2014 concerning Villages. This research is qualitative research with a normative juridical approach. This research will focus on the discussion of how to resolve election disputes for Village Heads in Indonesia after the issuance of Law No. 6 of 2014, and how problems arise due to the settlement of disputes over the results of the Village Head election after the issuance of Law No. 6 of 2014. The results show that Law No. 6/2014 has mandated that the settlement of Village Head election disputes that are settled by the Regent / Mayor is no later than 30 days after the determination of the Village Head candidate elected by the Village Head election committee, however in its implementation there are still problems, these problems can be seen from not regulating changes and settling disputes over the results of the Village Head election. In addition, the problem with the authority given to the Regent / Mayor to resolve disputes over the results of the Village Head election is when the Regent / Mayor is a state institution that has the power of the state in the executive, not the judiciary, the Regent / Mayor is also a product of political parties, so that the authority is given It is feared that the authority to implement disputes over the results of the Village Head election will not be objective. The conclusion of this research is to form a special judicial institution for disputes over the results of village head elections.Keywords: Labor Social Security, Parking Attendants, Department of Transportation